KINERJA PEGAWAI APARATUR SIPIL NEGARA DALAM PELAYANAN ADMINISTRASI DI KABUPATEN TAKALAR - Sukri, Muh Zaad; Abdi, Abdi; Hawing, Hardianto (Universitas Muhammadiyah Makassar, 2024)
The aim of the research is to determine the performance of State Civil Service Employees (ASN) in Administrative Services at the Mangarabombang District Office, Takalar Regency.